Efeitos do treinamento físico sobre a força muscular em adolescentes com obesidade submetidos à terapia interdisciplinar de emagrecimento e mudanças no estilo de vida de longo prazo - Moreira, Carlos Eduardo [UNIFESP] (2016)
The propose of study was to verify the role of long-term aerobic plus resistance training associated to interdisciplinary approach on isokinetic parameter and its impact on visceral adiposity. Forty postpubertal obese adolescents were involved in 1 year to interdisciplinary weight loss therapy. Body composition, visceral and subcutaneous fat were performed. Muscle strength was performed by isokinetic dynamometer. Interdisciplinary therapy effects were analyzed by t test. Correlations were established by Pearson´s and Spearman´s test. It were showed a significantly reduction in total body and mass; arms, leg, trunk, android and gynoid fat mass (%); visceral and subcutaneous fat (cm). Inversely, it was observed increased body lean mass (kg/%). Analyzing the isokinetic parameters it were showed some improvements in the peak of torque for all angles. To the total wok (J) variable, only significantly increase was observed for lower limbs. It is observed statistical changes for work fatigue (%) in lower limbs. Positive correlations were observed between peak torque with body lean mass in all angles performed and negative correlations with visceral fat and gynoid fat mass. Negative correlations were found between peak torque (N-M) with arms fat mass (%); peak torque (TQ/BW %) with subcutaneous fat (cm) and positive correlations with body lean mass (%). The muscle strength and fat distribution were improved in the present investigation and parameters of peak torque was positively with lean body mass and inversely correlated with visceral fat, showing the importance of aerobic plus resistance training to combat obesity and its consequences in the health.